Strategizing Regional Development in the Shaping of the Post-War Economic Landscape of the Regions of Ukraine - Zhalilo, Ya. A.; Snigova, O. Yu. (Ukrainian Geographical Journal, 2026)
The article examines the systemic impact of the full-scale war in Ukraine on the capacity of regional economic systems to engage the drivers of their development during the post-war recovery. A generalized assessment has been conducted of structural changes in the regions’ economies due to the war. Arguing that the construction of the spatial structure of the new economy will be subject to the impact of the objective characteristics of the current state of the territories, which will determine the allowable range of structural changes in the post-war period, the authors systematize the limitations for economic activity in certain territories, which influence the sectoral structure of regional economies, as well as the new resource opportunities, facing regions and communities and available to be involved in the construction of the new balanced sectoral and spatial structure of the economy. The category “economic landscape” is used to understand the interdependence between sectoral and spatial transformations. Assuming that sectoral and spatial heterogeneity of the economic landscape as a system predetermines the variability of its transformations, which are carried out under the impact of endogenous regularities of the development of the elements of this system, as well as of the exogenous effects, the authors ground the priorities of the strategy, which will promote creating the conditions for optimal engagement of the resource potential of the regions, considering its territorial distribution and spatial features. Such priorities include maximal inclusion of human capital of the territory in productive activity; involvement of new technologies to reveal the local resource potentials and to provide sectoral diversification of the drivers of regions’ economy development; practical elaboration and implementation of differentiated politics and instruments for territories, differentiated by levels of damage and security threats; and strengthening institutional and resource capacity and authority of local communities to create the conditions for local economies’ development.
Keywords: regional economy; regional policy; economic landscape; sectoral transformations; spatial transformations; resource potential